Sensorless speed Control based on Interconnected High Gain Observer for Induction Motor - Fethiza Tedjani, Tedjani; Gouacem, Raid Akram (Echahid Hama Lakhdar University of Eloued, 2019)
This project concerns the observation and control of the induction motor without speed sensor using an interconnected high gain observer, the main goal of this work is to construct, test and evaluate the performance of the mentioned observer associated with the sensorless field oriented control of induction motor. The concerned observer proposed to design the system in two subsystems one as estimator and the second as observer. The results obtained illustrate the good performance in term of robustness, despite the problems of unobservability when the motor runs at low speed.يتعلق هذا المشروع بالمراقبة والتحكم في المحرك الالتزامني بدون القط السرعة باستخدام مراقب ذو المعامل الكبير، والهدف الرئيسي هو إنشاء، اختباروتقييم أداء المراقب المذكور، والذي يرتبط بالتحكم بدون القط للمحرك الالتزامني.المراقب المقترح يعتمد أساسا على نظام ينطوي على نظاميين فرعيين، أحدهما يعمل كمقدر واآلخر يعمل كمراقب، توضح النتائج التي تم الحصول عليها األداء ييد من حي المتانة. على الرغم من مشاكل عدم القدرة على المالحظة عند تشغيل المحرك بسرعة منخفضة.
مذكرات ماستر تخصص تحكم
Keywords: Sensorless-Interconnected-Motor-Control based; يعتمد على التحكم في المحركات المترابط بدون مستشعر